STUDENTS’ TRANSFERABLE SKILLS COMPARISON BASED ON SPECIAL NEEDS, AGE, AND GRADE LEVEL - Fajriani Fajriani; Andre Julius; Rischa Pramudia Trisnani; Syaiful Bahri; Yulizar Yulizar (Universitas Pendidikan Indonesia, 2022)
Students with special needs deserve equal opportunities in terms of careers and jobs. Therefore, they need to prepare well, including having a skill called transferable skill. Transferable skills are considered an essential factor in achieving a career. Transferable skills are life skills that are the basis and need to face a future career. This study describes the transferable skills of students with special needs in terms of the type of special needs, age, and grade level. The study employed a quantitative approach with a survey method. This study was conducted at Special Education Schools (Public and Private) in Lhokseumawe City, Aceh Province. Respondents of the study were students of classes X and XI. Transferable skills are measured using a scale developed with three aspects: cognitive, affective, and psychomotor—a test of the validity and reliability of the instrument was also carried out. Descriptive statistics and Kruskal-Wallis Test analyzed data. The results of descriptive and comparative data analysis are presented in the findings section of the study. The Kruskal-Wallis test showed a significant difference in the average transferable skill score based on the type of special needs and grade level. At the same time, the age factor did not provide a significant difference. The results of this study have implications for the design of transferable skills development programs for students with special needs to enter the workplace or the social environment after graduating from Special Education School.Future research is expected to examine a broader range of respondents covering all categories of special needs, not only students with hearing impairment, intellectual disability, and autistic, as in this study.